Deep submerged speleothems in the Sansha Yongle Blue Hole (South China Sea) as determination of low sea levels during the Last Glacial Maximum - Yu, Xiaoxiao; Duan, Baichuan; Zhao, Jingyao; Gu, Dongqi; Feng, Aiping; Liu, Yanxiong; Li, Tiegang (Frontiers in Marine Science, 2022)
Although Last Glacial Maximum (LGM) sea levels have been the focus of much attention in climate and marine sciences, the timing, duration, and magnitude need further research. Here we present observations and analyses of the deepest speleothems (-116 m) collected from the deepest known blue hole on a global scale, the Sansha Yongle Blue Hole, Xisha Islands, South China Sea. The field investigations illustrate that submerged speleothems are irregular cauliflower-like coatings on the downward cave ceiling from water depths of 90 to 120 m. The downward growth direction and negative stable carbon and oxygen stable isotopes of submerged speleothems suggest that they may deposit in an air-filled condition through gravity drip, indicating the maximum LGM sea level. The deep submerged speleothems were dated, indicating two U–Th ages of 29.16 ± 0.17 and 26.04 ± 0.18 ka BP and one radiocarbon age of 18.64 ± 0.12 ka BP, respectively. The investigated deep submerged speleothems therefore clearly determine the minimum onset and maximum termination times for LGM terms of sea level. The results show that LGM began at 29 ka BP and ended at 18.5 ka BP. This study therefore provides initial evidence for the use of deep speleothems to determine LGM sea levels and emphasizes the importance of deep submerged speleothems in the reconstruction of Pleistocene low sea levels.